THE ROLE OF BELANTIK IN MARKETING BALI CATTLE IN BALI PROVINCE: A REVIEW - N. M. A. K., DEWI; SYAHLANI, S. P.; HARYADI, F. T. (Majalah Ilmiah Peternakan; Vol 27 No 1 (2024): Vol. 27 No. 1 (2024), 2024)
The marketing strategy needs serious attention because the marketing process with the right marketing channels can provide the best selling price because it has an impact on increasing farmers' income. In 1990, farmers implemented direct marketing channels. On the other hand, the last two decades have shown that farmers' dependence on belantik is higher compared to direct marketing channels. A study to identify the role of belantik needs to be carried out to determine the basis of livestock farmers' dependence on belantik as an intermediary in the marketing channel for Bali cattle in Bali Province. The method used is a literature review. The results of the study show that marketing of Bali cattle in Bali Province is still dominated by indirect marketing involving belantik to market livestock to inter-island traders and slaughterers. The high dependence of farmers on belantik is due to the farmers' weak bargaining power, such as small livestock ownership scale, high transportation costs, unavailability of capital, livestock as a side business, lack of entrepreneurial spirit, no livestock price standards, and farmers lack skills in estimating body weight which allows livestock not to be sold or sold at low prices. This condition shows that belantik has quite an important role in marketing bali cattle in Bali Province.